Private sector quality interventions to improve maternal and newborn health in low- and middle-income countries: a scoping review - Jung, Anne-Sophie; Yaqub, Nuhu; Lattof, Samantha R.; Strong, Joe; Maliqi, Blerta (Frontiers in Public Health, 2025)
IntroductionThe private health sector provides significant maternal and newborn health (MNH) services in mixed healthcare systems in many low- and middle-income countries (LMICs), making it an essential partner in achieving universal health coverage (UHC). Although some studies have mapped the private sector’s activities in MNH care in LMICs, limited knowledge exists about specific quality of care interventions. This scoping review addresses this gap by mapping quality of care interventions implemented by private healthcare providers for MNH care in LMICs.MethodsFollowing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR), nine electronic databases were searched. Studies were included if they examined an intervention primarily designed to deliver MNH care by the private sector in LMICs.ResultsA total of 11,922 titles and abstracts were screened, with 38 meeting the inclusion criteria. Qualitative and quantitative data were extracted for descriptive statistics and thematic analysis, focusing on maternal mortality, maternal morbidity, newborn mortality, newborn morbidity, quality of care, experience of care, private sector care usage, and stillbirth. Findings are presented as a systematic narrative synthesis using the WHO’s National Quality Policy and Strategy (NQPS) framework’s quality intervention groups. While various interventions exist, public–private partnership (PPP) schemes and vertical programmes have received more scholarly attention. Most studies emphasised health outcome indicators.DiscussionWe argue that outcome reporting should be diversified to include stakeholders’ perspectives, helping researchers and policymakers understand how governments can engage the private sector in sustainable partnerships that strengthen health systems and advance UHC with quality. Interventions should be people-centred, incorporating feedback mechanisms that promote accountability and empower intended beneficiaries.